3D fluorescent mapping of invisible molecular damage after cavitation in hydrogen exposed elastomers. Issue 16 (16th April 2021) - Morelle, Xavier P.; Sanoja, Gabriel E.; Castagnet, Sylvie; Creton, Costantino
Abstract : Elastomers saturated with gas at high pressure suffer from cavity nucleation, inflation, and deflation upon rapid or explosive decompression. Abstract : Elastomers saturated with gas at high pressure suffer from cavity nucleation, inflation, and deflation upon rapid or explosive decompression. Although this process often results in undetectable changes in appearance, it causes internal damage, hampers functionality ( e.g., permeability), and shortens lifetime. Here, we tag a model poly(ethyl acrylate) elastomer with π-extended anthracene–maleimide adducts that fluoresce upon network chain scission, and map in 3D the internal damage present after a cycle of gas saturation and rapid decompression. Interestingly, we observe that each cavity observable during decompression results in a damaged region, the shape of which reveals a fracture locus of randomly oriented penny-shape cracks ( i.e., with a flower-like morphology) that contain crack arrest lines. Thus, cavity growth likely proceeds discontinuously ( i.e., non-steadily) through the stable and unstable fracture of numerous 2D crack planes. This non-destructive methodology to visualize in 3D molecular damage in polymer networks is novel and serves to understand how fracture occurs under complex 3D loads, predict mechanical aging of pristine looking elastomers, and holds potential to optimize cavitation-resistance in soft materials.